2021
DOI: 10.1097/hco.0000000000000868
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of hypertension, obesity, left ventricular hypertrophy, and heart failure

Abstract: Purpose of reviewHypertension (HTN) and obesity are major risk factors for cardiac remodeling and dysfunction, leading to left ventricular hypertrophy (LVH) and heart failure (HF). In this review, we discuss the complex mechanisms and effects of HTN and obesity, and their treatments in LVH, ventricular function, and HF. Recent findingsObesity and HTN impact the heart through overlapping neurohormonal pathways. However, the relationship between obesity and cardiomyopathy is more complex, and additional metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“… 1 , 2 In many studies, factors that determine the clinical course of CS were evaluated and various risk factors were shown to contribute to negative outcomes. 3 Obesity, one of the risk factors traditionally known to be associated with worse outcomes in patients with heart failure (HF), 4 was also reported to contribute to negative outcomes in CS. 5 , 6 …”
mentioning
confidence: 99%
“… 1 , 2 In many studies, factors that determine the clinical course of CS were evaluated and various risk factors were shown to contribute to negative outcomes. 3 Obesity, one of the risk factors traditionally known to be associated with worse outcomes in patients with heart failure (HF), 4 was also reported to contribute to negative outcomes in CS. 5 , 6 …”
mentioning
confidence: 99%
“…Algahim et al found a significant regression in LVM and LVMI after bariatric surgery and suggested that this change is modulated by neurohumoral factors that may improve long-term survival [ 38 ]. Without significant weight loss, the reversal of left ventricular remodeling is also generally not achieved by blood pressure control alone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is one of the most critical risk factors for atherosclerotic cardiovascular disease, type 2 diabetes, and other metabolic diseases, leading to the loss of nearly 20 years of life [ 2 4 ]. Weight loss helps improve ventricular remodeling and heart failure [ 5 ]. The metabolic complications of obesity are more closely related to visceral obesity than overall obesity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the obese group in this study had a higher mean LV ejection fraction, a strong relationship was observed between obesity, cardiomyopathy, and heart failure. Normalization of the left ventricular mass in obese and hypertensive individuals requires both normotension and weight loss [14].…”
Section: Discussionmentioning
confidence: 99%